2020
DOI: 10.1242/jeb.217117
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a high-fat diet in mice is dependent on duration and age, and differs between muscles

Abstract: Prolonged high-fat diets (HFDs) can cause intramyocellular lipid (IMCL) accumulation that may negatively affect muscle function. We investigated the duration of a HFD required to instigate these changes, and whether the effects are muscle specific and aggravated in older age. Muscle morphology was determined in the soleus, extensor digitorum longus (EDL) and diaphragm muscles of female CD-1 mice from 5 groups: young fed a HFD for 8 weeks (YS-HFD, n=16), young fed a HFD for 16 weeks (YL-HFD, n=28) and young con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 82 publications
6
52
1
Order By: Relevance
“…It is interesting to note that although a HFD led to a lower amount of food intake, the caloric intake was elevated in both young and old mice. Similar to previous observations the higher caloric intake was accompanied by an increase in body mass 29 . It was somewhat surprising, however, that the increase in body mass was greater in young than old mice, as in a previous study old mice had a larger gain in body mass 29 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is interesting to note that although a HFD led to a lower amount of food intake, the caloric intake was elevated in both young and old mice. Similar to previous observations the higher caloric intake was accompanied by an increase in body mass 29 . It was somewhat surprising, however, that the increase in body mass was greater in young than old mice, as in a previous study old mice had a larger gain in body mass 29 .…”
Section: Discussionsupporting
confidence: 91%
“…Similar to previous observations the higher caloric intake was accompanied by an increase in body mass 29 . It was somewhat surprising, however, that the increase in body mass was greater in young than old mice, as in a previous study old mice had a larger gain in body mass 29 . The discrepancy may be attributable to the duration of HFD, as it has been observed that old mice become more easily obese than young in response to a short-term HFD, whereas chronic HFD feeding causes greater body mass increase in young than old mice 30 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Limit the processing of fatty acids to 2C fragments and thus dump them as TAG (with a token 3C glycerol) [ 200 ]. This process induces obesity [ 201 ], steatosis [ 202 ], and drives muscle to be essentially a fat-infiltrated 2C energy user, with glucose intolerance [ 203 , 204 ].…”
Section: The Triad Of Main Energy Sources and How Sorting Of Subsmentioning
confidence: 99%
“…Although the mouse strain CD1 has been widely used to examine multiple aspects of the general aging process [15][16][17], its alveolar morphometric analysis has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%